Tax Appeal: A Proposal to Make the United States Tax Court More Judicial - Leandra Lederman (Washington University Law Review, 2008)
This Article argues that rather than leaving the Tax Court to its own devices, Congress should recognize the entirely judicial nature of the Tax Court by making it subject to the AOUSC; the Rules Enabling Act; and, with respect to its rulemaking, the Judicial Conference. These straightforward but important structural changes should decrease the Tax Court’s insularity, increase its accountability, and help reduce inefficiencies. These changes also would help increase the respect accorded the Tax Court. The Article proceeds in three principal parts. Part I focuses on the fundamental question of the extent to which the Tax Court truly is a court. The Tax Court officially ceased to be an administrative agency in 1969. Yet, in many ways, the Tax Court is still not really a “federal court.” This Part explores some of the ways in which the Tax Court has been overlooked and the unfortunate consequences that result. Part II of the Article discusses areas in which the Tax Court has followed procedures that are unusual in their lack of transparency. Some of these areas became apparent in the fallout from Ballard v. Commissioner, the high-profile, multi-million-dollar tax fraud case mentioned earlier, which was decided by the Supreme Court in 2005. Other transparency issues predate Ballard. Part III proposes to remedy an important anomaly in the federal system by treating the Tax Court like other courts, thereby increasing the Tax Court’s accountability. This would not require remaking the Tax Court as an Article III court, a change that would entail giving Tax Court judges life tenure and would likely raise controversial issues that are unnecessary for Congress to face. Instead, the Tax Court should be subject to the judicial institutions that already govern courts such as the Article I Court of Federal Claims. Part III also explains the efficiency and other benefits of this proposal.
Keywords: Tax courts; United States. Tax Court; Judicial review; Tax appeals; Court records; Estate of Ballard v. Commissioner No. 01-17249 (11th Cir. Apr. 7, 2008)